PROBLEMS OF INTERNATIONAL OPINION SURVEYS - RADVANYI, LASZLO (Departamento Fitosanitario, San Jacinto, CD MEXICO, DF, MEX, 1941)
If international opinion surveys are to be made inclusive of all areas and cultures, the problems of question meaning, different attitudes toward polls, sampling and interviewing will become more significant and difficult Different traditions, socio-econ
INT J OPINION ATTITUDE RES
Keywords: PROBLEMS, INTERNATIONAL, OPINION SURVEYS; CIENCIA POLITICA; OPINION PUBLICA; MEDIOS DE COMUNICACIÓN DE MASAS